Cytochrome 2B6 polymorphism and efavirenz‐induced central nervous system symptoms : a substudy of the ANRS ALIZE trial. Issue 8 (1st February 2017) - Gallien, S; Journot, V; Loriot, M‐A; Sauvageon, H; Morlat, P; Reynes, J; Reliquet, V; Chêne, G; Molina, J‐M; ,
Abstract : Objectives: Single nucleotide polymorphisms in the cytochrome P450 ( CYP ) 2B6 gene have been associated with high interindividual variation in efavirenz pharmacokinetics. However, clinical data on the relationship of CYP2B6 polymorphisms with the occurrence of efavirenz‐induced central nervous system (CNS) symptoms are limited. Methods: We analysed four polymorphisms in the CYP2B6 (516 G>T), CYP3A5 (6986 A>G) and ATP‐binding cassette, sub‐family B, member 1 (ABCB1) (2677 G>T/A and 3435 C>T) genes in HIV‐infected adults virologically suppressed on a protease inhibitor‐based regimen who switched to a regimen containing emtricitabine, didanosine and efavirenz in the setting of the ANRS ALIZE trial. Kaplan−Meier methods and Cox regression analysis were used to investigate their association with efavirenz plasma levels and CNS events up to 48 months after switching. Results: In total, 191 patients with a median age of 41 years, who were 87% male and 85% Caucasian, were enrolled in the study. Variant allelic frequencies were 0.49, 0.93, 0.59 and 0.63 for CYP2B6 516, CYP3A5 392, ABCB1 2677 and ABCB1 3435, respectively. The median efavirenz plasma concentration (MEPC) was 2.2 mg/L [interquartile range (IQR) 1.7–2.8 mg/L] and was significantly higher in patients with the deficient CYP2B6 516T. Overall, 242 CNS events were reported in 104 individuals (54%). No correlation was found between MEPC and CNS events. The occurrence of a first CNS event was lower in patients with the CYP2B6 516 G/G genotype vs . CYP2B6 516 T genotypes [50% (IQR: 40–60%) vs . 66% (IQR: 56–75%), respectively; P = 0.02]. In an adjusted Cox regression model, there was a tendency towards a higher risk of a first CNS event among carriers of the variant CYP2B6 516 T allele (relative risk 1.4 [95% CI, 0.99–2.1]; P?=?.06), compared with noncarriers. Conclusions: The deficient CYP2B6 516 T allele is associated with higher efavirenz plasma drug levels and more frequent CNS‐related symptoms.